An Emergency Department Experience with Tele-Triage to Manage the Surge of COVID-19 Related Visits - Waddaa Reda; Ibtihal M. Alattas; Yassar K. Kamal; Fahad A. Alzahrani; Yousef Aledreesi; Sultan A. Alwajeeh (Journal of King Abdulaziz University: Medical Sciences, 2021)
In March 2020, the World Health Organization declared COVID-19 a pandemic. Since then, the number of cases worldwide has increased rapidly, causing panic and leading to an increase in patients visiting emergency departments. A key factor in slowing the transmission of COVID-19 is social distancing through decreasing person-to-person contact. Using a telemedicine technique to score and triage patients according to their symptoms might help to limit unnecessary emergency department visits and decrease the risk of exposure to COVID-19. In Saudi Arabia, the increase in the number of cases has stressed many emergency departments. At King Abdulaziz University Hospital, a tele-triage program was used to screen patients, with the goal of limiting unnecessary visits to the emergency departments for screening or information. Based on self-reported data, a 27% drop in the number of people planning to visit the emergency departments for COVID-19-related complaints was registered in the initial month. Research also suggests that involving telemedicine in routine practice could ease its implementation during a pandemic or disaster. The article describes the program’s rationale, the protocol developed, and the results of statistical analysis of the first month’s data, as well as some of the challenges faced in implementing such a program and in drawing conclusions.